Nitrous oxide in seawater during Lomrog III cruise, Arctic Ocean (2012) - Laura Farías; Josefa Verdugo (PANGAEA, 2025)
The concentration of nitrous oxide (N2O), along with temperature and salinity, were measured in the ice- covered Arctic Ocean within the Eurasian Basin (Verdugo et al., 2016; doi:10.1016/j.dsr.2016.08.016). The transect was conducted across the Nansen-Gakkel Ridge, from the Nansen Basin to the Amundsen Basin, covering depths from the surface (10 m) down to 4300 m. All sampling stations, except for ST 12, were covered by sea ice. Water samples were collected with a CTD-rosette sampler equipped with 24 Niskin Bottles. Gas sampling was carried out directly from 12 L Niskin bottles. Triplicate water samples for N2O analyses were taken in 20 mL glass vials and preserved with 50 μL of saturated HgCl2. The vials were then sealed with a butyl-rubber septum and an aluminum cap to prevent bubble formation and stored in darkness at room temperature until laboratory analysis. N2O concentrations were analyzed by creating 5 mL of ultra-pure helium headspace, followed by equilibration in the vial, and then quantified with a gas chromatograph (GC). A Shimadzu 17A GC equipped with an electron capture detector (ECD) maintained at 350 °C, and a capillary column operated at 60 °C was used for analysis. The GC was connected to an autosampler device (Farías et al., 2009; doi:10.5194/bg-6-3053-2009). A calibration curve was made with three standard concentrations for N2O (0.1, 0.5 and 1 ppm, provided by Scotty Standards) and dry air.